Happening, a Controversial Hybrid Way of Cultural Expression - HEDEȘ, Bianca (Studia Universitatis Babeș-Bolyai Dramatica, 2022)
The aim of this article is to explore an experimental acting exercise that took place in 2015 during a survival workshop guided by the Romanian-Canadian stage director Alexander Hausvater. The name of the workshop was “The total actor – The survival” and took place in Colibița, a mountain resort in Bistrița-Năsăud county involving 25 young actors. The actors embodied different human typologies for almost 12 hours in the town of Bistrița. The exercise was conducted in different areas of the town and each actor was supposed to remain in the “skin” of the character no matter the circumstances. Even though they interacted with civilians from the urban environment, they had to continue to exhibit the traits and features assigned to the character as if they were on stage. Many of the citizens were taken in by the deceitful appearances and believed that the actors they interacted with were real people with real issues. The closeness between reality and pretence was so tight that some of the spectators insisted on helping the needy, underprivileged typologies some of them were interpreting. Consequently, the difficulty in going on with the acting part became even harder for the participants in the workshops because of this interference. The main purpose of this type of exercise was to point out the complexity an actor is capable of and the involvement s/he must show in front of a changing audience, with a nonconformist moving stage. Were the actors able to prove the director’s expectations according to his given definition of a true actor? Were the actors ready enough to exploit previously unpaved roads? Was this type of practice beneficial to achieve the ultimate goal? Is happening the best way of showing the mixture of abilities an actor has?